Sources of Charged Higgs Pair through Double or Triple Higgs Production at Linear Colliders - Ijaz Ahmed (Advances in High Energy Physics)
The production of triple Higgs (H+H-H0), (H+H-h0) and pairwise charged Higgs boson (H+H-) is studied in the context of future linear colliders within the two-Higgs-doublet model (2HDM) type II. The aim is to compare sources of charged Higgs pair through the above processes, that is, double and triple Higgs production. Cross sections are calculated at the leading order in 2HDM type II and Minimal Supersymmetric Standard Model (MSSM). Several orders of magnitude (~104) enhancement are observed in 2HDM compared to MSSM, while no sizable enhancement is seen in muon collider versus electron-positron collider. The analysis is based on a heavy charged Higgs with mass above 500 GeV. It is found that double charged Higgs production cross section (being the same in 2HDM and MSSM) is few femtobarns, while the triple Higgs production cannot exceed a fraction of femtobarn within the parameter space under study.